Stress-Protective Role of Dietary α-Tocopherol Supplementation in Longfin Yellowtail (Seriola rivoliana) Juveniles - Gloria Gertrudys Asencio-Alcudia; Cesar Antonio Sepúlveda-Quiroz; Juan Carlos Pérez-Urbiola; María del Carmen Rodríguez-Jaramillo; Andressa Teles; Joan Sebastián Salas-Leiva; Rafael Martínez-García; Luis Daniel Jiménez-Martínez; Mario Galaviz; Dariel Tovar-Ramírez; Carlos Alfonso Alvarez-González (Fishes, 2023)
Aquaculture practices expose fish to several factors that may generate stress, modifying the balance between the production of reactive oxygen species (ROS) and the activity of antioxidant defenses that induce cell damage. Alpha-tocopherol (VE) improves the antioxidant capacity against ROS production in fish. A 50-day trial with longfin yellowtail (Seriola rivoliana) juveniles was conducted to compare the dietary supplementation of 500 mg/kg of VE against a control diet without VE supplementation on growth, lymphoid tissue enzymatic activity, immune-system-related gene expression, and the histology of the liver and spleen. Growth, weight gain, specific growth rate, feed conversion rate, and survival did not show significant differences (p > 0.05) among treatments. Fish fed with an α-tocopherol-enriched diet showed a higher enzymatic activity of superoxide dismutase in the liver (p < 0.05) and a lower percentage of melanomacrophage coverage area in the lymphoid organs (p < 0.05). Overexpression was observed of MyD88 and il-10 in the spleen, and il-1b in the liver in fish fed 500 mg/kg of VE, as well as overexpression of Toll-like 3 in the head kidney, spleen, and liver in fish fed the control diet. Dietary supplementation with VE reduces the effects of oxidative stress and improves lymphoid tissue defense and immune-related gene expression in S. rivoliana.